Small Bowel Obstruction Secondary to Interstitial Hernia: Laparoscopic Approach. (21st October 2015) - Alvarez Gallesio, J. M.; Schlottmann, F.; Sadava, E. E.
Abstract : Interstitial hernias are a rare entity. Most of them are detected incidentally on imaging studies. We present a case of abdominal bowel obstruction secondary to interstitial hernia on the fifth postoperative day of an open incisional hernia repair. Laparoscopy confirmed the diagnosis and led to an accurate treatment avoiding a new laparotomy. In this case, prompt surgical decision based on clinical and CT scan findings allowed a mini-invasive approach with satisfactory outcome.